Characterization of Selected Soybean Germplasm through Fatty Acid and Oil Composition using Near-Infrared Spectroscopy: The chemistry of Pakistani soybean germplasm - Gul, Nazish; Ullah, Inam; Murtaza, BiBi Nazia; Khan, Waqar; Ali, Azam (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Soybean belongs to legumes and is said to be one of the best sources of oil and fats. The objective of this research was to identify specific and individual accession among the fifty soybean accessions collected from Plants Genetics Research Institute (PGRI) Islamabad for oil contents and fatty acids profile using near-infrared reflectance spectroscopy. The amount of oil content in 50 soybean accessions was recorded in the range of 13.816-23.40 % among which accessions 017421, 17423, 17430, 17435, and 17459 were found with the highest percentage of 23.4 %, 22.80 %, 22.214 %, 22.105 %, and 22.08 % respectively. The values of fatty acid content in these accessions for palmitic acid (16:0), stearic acid (18:0), oleic acid (18:1), linoleic acid (18:2) and linolenic acid (18:3) ranged between 10.077-18.48%, 1.95-5.88 %, 18.204-30.12 %, 22.756-53.879 % and 4.714-9.96 % respectively. Soybean accessions observed higher for oil content are recommended for cultivation; where it is grown for oil production. Based on essential fatty acids contents, accessions 017418 and 017420 are recommended for a future breeding program to improve human health. Due to the variability identified in the present research, it is critical to select single Soybean accession having all the traits for further breeding programs until a specific trait is chosen.